2009
DOI: 10.1080/15374410902851630
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Integration of the Hopelessness and Response Styles Theories of Depression in Middle Adolescence

Abstract: The current study examined several theories of depression in a sample of middle adolescents. At Time 1, 367 ninth graders completed measures assessing depressogenic inferential styles, the tendency to ruminate in response to depressed mood, and depressive symptoms. Six weeks later, participants completed measures assessing negative events and depressive symptoms. In line with the hopelessness theory, a depressogenic weakest link interacted with negative events to predict increases in hopelessness depression sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 42 publications
10
59
2
Order By: Relevance
“…Neither of these predictive relationship varied as a function of gender, however, female adolescents did report a greater tendency to ruminate in response to stress than males. This is line with previous studies that have found a significant gender difference in levels of rumination among adolescents (Abela et al 2008;Schwartz and Koenig 1996). Support was not obtained for fluctuations in general depressive symptoms as a mediator of the relationship negative events and substance misuse.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Neither of these predictive relationship varied as a function of gender, however, female adolescents did report a greater tendency to ruminate in response to stress than males. This is line with previous studies that have found a significant gender difference in levels of rumination among adolescents (Abela et al 2008;Schwartz and Koenig 1996). Support was not obtained for fluctuations in general depressive symptoms as a mediator of the relationship negative events and substance misuse.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a study examining reactions to a college midterm exam found that rumination and exam results did not interact to predict depressive symptoms over time (Sarin et al 2005). Although Abela et al (2008) found that that the main effect of rumination prospectively predicted increases in depressive symptoms in a sample of ninth graders, they did not find a significant interaction between rumination and negative events. Also failing to provide support for a diathesis-stress conceptualization, Schwartz and Koenig (1996) reported that the interaction between rumination and negative events failed to predict increases in depressive symptoms at a 6-week follow-up in a sample of adolescents.…”
Section: Self-focused Attention and Depressionmentioning
confidence: 72%
“…Past research in support of the moderating role of rumination has demonstrated that a stronger relationship between stress and depressive symptoms exists for adolescents who engage in higher rates of rumination (Kraaij et al 2003). In contrast, other researchers (Abela et al 2009;Jose and Brown 2008;Schwartz and Koenig 1996) fail to find significant evidence of the moderating effect of rumination on the relationship between stress and depressive symptoms. Given the small set of extant studies and their resultant mixed findings, more research is needed examining the relationship between rumination and depression within a vulnerability-stress model.…”
Section: Rumination As a Moderator Of The Relationship Between Stressmentioning
confidence: 83%
“…Young children are capable of drawing inferences about events and evidence potential for demonstrating a stable attributional style. In one study, third graders demonstrated greater pessimism in their attributions than seventh graders, were more likely to catastrophize, and viewed themselves as flawed following negative life events (Abela & Payne, 2003). Consistent with prediction, the interaction of life events and attributional style appears to be a more potent predictor of depression as children age (Abela, 2001;Conley, Haines, Hilt, & Metalsky, 2001;Nolen-Hoeksema, Girgus, & Seligman, 1992).…”
Section: Reviewmentioning
confidence: 88%
“…In an investigation of this hypothesis among seventh graders, the interaction of life stress by weakest link predicted increases in hopelessness depression symptoms (Abela & Sarin, 2002). Recent tests of this model are also supportive (Abela & Payne, 2003;Abela et al, 2006). As such, the weakest link hypothesis represents a refinement of attributional models of cognitive vulnerability, but would be strengthened through: 1) explication of why a child would develop one weak link, as opposed to another, and 2) how a child's weakest link may vary over time and across settings.…”
Section: Reviewmentioning
confidence: 99%